Figure 10 from: Sheffield CS, Oram R, Heron JM (2020) Bombus (Pyrobombus) johanseni Sladen, 1919, a valid North American bumble bee species, with a new synonymy and comparisons to other "red-banded" bumble bee species in North America (Hymenoptera, Apidae, Bombini). ZooKeys 984: 59-81. https://doi.org/10.3897/zookeys.984.55816 - Sheffield, Cory S.; Oram, Ryan; Heron, Jennifer M. (Zenodo, 2020)
Figure 10 Distribution map of known specimens of B. johanseni, including B. interacti. Specimens identified in the literature as B. gelidus are also included as it is likely that some of these, especially the eastern record, are actually B. johanseni, and not dark specimens of B. sylvicola.